An uncertainty principle for star formation – V. The influence of dust extinction on star formation rate tracer lifetimes and the inferred molecular cloud lifecycle. Issue 4 (25th July 2020) - Haydon, Daniel T; Fujimoto, Yusuke; Chevance, Mélanie; Kruijssen, J M Diederik; Krumholz, Mark R; Longmore, Steven N
ABSTRACT: Recent observational studies aiming to quantify the molecular cloud lifecycle require the use of known 'reference time-scales' to turn the relative durations of different phases of the star formation process into absolute time-scales. We previously constrained the characteristic emission time-scales of different star formation rate (SFR) tracers, as a function of the SFR surface density and metallicity. However, we omitted the effects of dust extinction. Here, we extend our suite of SFR tracer emission time-scales by accounting for extinction, using synthetic emission maps of a high-resolution hydrodynamical simulation of an isolated, Milky Way-like disc galaxy. The stellar feedback included in the simulation is inefficient compared to observations, implying that it represents a limiting case in which the duration of embedded star formation (and the corresponding effect of extinction) is overestimated. Across our experiments, we find that extinction mostly decreases the SFR tracer emission time-scale, changing the time-scales by factors of 0.04–1.74, depending on the gas column density. UV filters are more strongly affected than H α filters. We provide the limiting correction factors as a function of the gas column density and flux sensitivity limit for a wide variety of SFR tracers. Applying these factors to observational characterizations of the molecular cloud lifecycle produces changes that broadly fall within the quoted uncertainties, except at high kpc-scale gas surface densities ($Σ _{\rm g}\gtrsim 20~{\mathrm{M_{\odot }\, pc^{-2}}}$ ). Under those conditions, correcting for extinction may decrease the measured molecular cloud lifetimes and feedback time-scales, which further strengthens previous conclusions that molecular clouds live for a dynamical time and are dispersed by early, pre-supernova feedback.